Kajian Yuridis Terhadap Perkawinan dibawah Umur - Rahajaan, Jakobus Anakletus; Niapele, Sarifa (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
Abstract Conducted research related to underage marriage, namely in the form of a juridical review using normative legal research methods, which analyze the provisions of laws and regulations related to the minimum age limit for a person. who can be granted permission to carry out the marriage. The results of our research can be abstracted as follows: Marriage is a very important and even sacred event in human life. A legal marriage, the requirements, among others, must meet the principle of consensualism or agreement (agreement) of the parties, as stated in article 6 paragraph 1 of the Marriage Law which reads,